Implementasi Algoritma Knuth Morris Pratt di Pencarian Data Asosiasi UMKM Provinsi Bengkulu - Eka Sahputra; Franki Ade Putra Franki; Yetman Erwadi (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2024)
The development of technology changes the way of view, the way of human interaction and how to utilize information technology for several needs. The application of the digital archiving information system at the Micro, Small and Medium Enterprises Association, abbreviated as MSMEs, is very helpful for micro, small and medium enterprises in recording information data for a long time that can be accessed by everyone quickly, anywhere and anytime as long as it is connected to the internet network. Data search is carried out using the Knuth Morris Pratt algorithm abbreviated as KMP in the process of searching data by matching patterns or word arrangements typed in search engines on the system. The Knuth Morris Pratt algorithm eliminates unnecessary comparison of patterns with text with precomputed tables that allow patterns to pass through as many positions as possible. The purpose of this study is the application of the Knuth Morris Pratt Algorithm in the Data Search Application of the MSME Association of Bengkulu Province. This research also produced a data search application for the MSME association of Bengkulu Province with a fast and reliable data search system with an accuracy rate of 100 percent. In the assessment of the System Usability Scale aspect, it received a score of 77 with a good predicate. This means that the Bengkulu MSME Association Data Search Application received a good response from the members of the association/users of the system. For the test results, OKTAVIA data search at the Pattern position [1,2,3,4,5,6,7] and string [9,10,11,12,13,14,15].